2022
DOI: 10.1039/d2nr02796h
|View full text |Cite
|
Sign up to set email alerts
|

In silico design of single transition metal atom anchored defective boron carbide monolayers as high-performance electrocatalysts for the nitrogen reduction reaction

Abstract: The development of low−cost and high−efficiency single atom catalysts (SACs) is essential for catalyzing nitrogen reduction reactions (NRR) under ambient conditions. Current SACs suffer from low selectivity and poor activity,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In our previous work, a structural descriptor φ was proposed as a symbol of catalyst performance for various inherent properties, including the active center. 34 The descriptor φ is defined as follows: φ = θ d × ( χ TM + 2 × χ C + χ B )/ χ O , where χ TM , χ C , χ B and χ O represent the electronegativity of the TM, C, B, and O elements, respectively, and θ d denotes the d-electron number of the TM atom. The calculated φ -values and the corresponding catalytic performances are depicted as points in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, a structural descriptor φ was proposed as a symbol of catalyst performance for various inherent properties, including the active center. 34 The descriptor φ is defined as follows: φ = θ d × ( χ TM + 2 × χ C + χ B )/ χ O , where χ TM , χ C , χ B and χ O represent the electronegativity of the TM, C, B, and O elements, respectively, and θ d denotes the d-electron number of the TM atom. The calculated φ -values and the corresponding catalytic performances are depicted as points in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that carbon vacancies are more likely to form on a BC 3 monolayer than boron vacancies. 33,34 Thus, for CO 2 RR, 12 TM atoms are doped into carbon vacancies to create SACs denoted as TM@BC 3 , as shown in Fig. 1(a).…”
Section: Structure and Stability Of Tm-doped Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-noble metal single-atom catalysts (SACs) with their metal-nitrogen-carbon coordination, namely, the so-called MN 4 structure have attracted the attention of many researchers in recent years, due to their full metal utilization, superior catalytic activity, and affordable price. [8][9][10][11][12] A similar local coordination environment in such MN 4 catalysts makes it easier to identify the active sites for accurate and insightful theoretical predictions. 13 On the other hand, a similar coordination environment also underlies the intrinsic electronic structure of the active sites-this makes it difficult to break the linear relationship between the catalytic activity and the adsorption energies of reaction intermediates in multi-step reactions, thus further hindering the possibility of improving their activities.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Many 2D materials show excellent performance as anode materials, for example nonmetallic element-based materials, like carbon, [14][15][16] boron, [17][18][19][20] phosphorus, 21,22 and binary compounds formed by the main group elements. 23,24 The stabilities and electronic conductivities of these compounds are improved by the addition of special metal ions. 25,26 Early transition metal carbides and carbonitrides (called MXenes) and orthorhombic transition metal borides (MBenes) have remarkable applications in electrode materials.…”
Section: Introductionmentioning
confidence: 99%